+0  
 
0
64
1
avatar

(x) = log3 (x + 1)

f-1 (x) = ?

 

(x) = ln(x)

f-1 (x) = ?

Guest Mar 6, 2017
Sort: 

1+0 Answers

 #1
avatar+75352 
+5

y = log3 ( x + 1)       we can write

 

3^y   = x + 1      subtract 1 from both sides

 

3^y - 1   = x      swap x, y

 

3^x - 1   = y       for y, write f-1(x)

 

f-1(x)  = 3^x - 1

 

 

y = ln(x)    exponentiate both sides

 

e^y = e^(ln x)

 

e^y = x     swap x, y

 

e^x  = y       for y, write f-1(x)

 

e^x = f-1(x)

 

 

cool cool cool

CPhill  Mar 6, 2017

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details